Kaposi’s Sarcoma Herpesvirus Genome Persistence - Juillard, Franceline; Tan, Min; Li, Shijun; Kaye, Kenneth M. (Frontiers in Microbiology, 2016)
Kaposi’s sarcoma-associated herpesvirus (KSHV) has an etiologic role in Kaposi’s sarcoma, primary effusion lymphoma and multicentric Castleman’s disease. These diseases are most common in immunocompromised individuals, especially those with AIDS. Similar to all herpesviruses, KSHV infection is lifelong. KSHV infection in tumor cells is primarily latent, with only a small subset of cells undergoing lytic infection. During latency, the KSHV genome persists as a multiple copy, extrachromosomal episome in the nucleus. In order to persist in proliferating tumor cells, the viral genome replicates once per cell cycle and then segregates to daughter cell nuclei. KSHV only expresses several genes during latent infection. Prominent among these genes, is the latency-associated nuclear antigen (LANA). LANA is responsible for KSHV genome persistence and also exerts transcriptional regulatory effects. LANA mediates KSHV DNA replication and in addition, is responsible for segregation of replicated genomes to daughter nuclei. LANA serves as a molecular tether, bridging the viral genome to mitotic chromosomes to ensure that KSHV DNA reaches progeny nuclei. N-terminal LANA attaches to mitotic chromosomes by binding histones H2A/H2B at the surface of the nucleosome. C-terminal LANA binds specific KSHV DNA sequence and also has a role in chromosome attachment. In addition to the essential roles of N- and C-terminal LANA in genome persistence, internal LANA sequence is also critical for efficient episome maintenance. LANA’s role as an essential mediator of virus persistence makes it an attractive target for inhibition in order to prevent or treat KSHV infection and disease.